A system operator's utility function for the frequency response market. (1st December 2018) - Greve, Thomas; Teng, Fei; Pollitt, Michael G.; Strbac, Goran
Highlights: Modelling the preference/utility function of a system operator in the market for electricity ancillary services. The utility function is combined of exchange rates in monetary values between different frequency response services. The exchanges rates are used in an auction mechanism to sell frequency response services. The mechanism delivers the welfare optimal mix of speed of frequency response and quantity to procure. We show that this mechanism is the efficient way to support new faster sources of frequency response. Abstract: How can the electricity system operator determine the optimal quantity and quality of electricity ancillary services (such as frequency response) to procure in a market increasingly characterized by intermittent renewable electricity generation? The paper presents a system operator's utility function to calculate the exchange rates in monetary values between different frequency response products in the electricity system. We then use the utility function in a two-sided Vickrey-Clarke-Groves (VCG) mechanism combined of two frequency response products – enhanced and primary – in the context of the system in Great Britain. This mechanism would allow the market to reveal to the system operator the welfare optimal mix of speed of frequency response and quantity to procure. We show that this mechanism is the efficient way to support new faster sources of frequency response, such as could be provided by grid scale batteries.